Neutrophil-to-lymphocyte and platelet-to-lymphocyte ratios as inflammation markers in patients with papilledema due to idiopathic intracranial hypertension - Ceylan, Osman Melih (Indian J Ophthalmol, 2021)
PURPOSE: The aim of this study was to investigate the role of inflammation in the pathogenesis of idiopathic intracranial hypertension (IIH) using the neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) as inflammation markers. METHODS: The files of 33 IIH patients and 33 controls were screened for this retrospective study. For each patient, the NLR and PLR values were calculated using a single fasting blood sample. For both eyes, papilledema (PE) grades, best-corrected visual acuity (BCVA), retinal nerve fiber layer thickness (RNFLT), and ganglion cell layer thickness (GCLT) measurements were recorded along with the demographic data, including body mass index (BMI), and complete neurological and ophthalmological findings. Comparisons between the two groups and between the IIH patients with and without PE were made. The associations of NLR and PLR with all other parameters were analyzed independently from age, gender, and BMI. RESULTS: NLR and PLR were higher in patients with IIH than controls (P < 0.05). They were also higher in patients with PE (P < 0.05) in the IIH group. NLR and PLR were found to be associated with BCVA (P < 0.001 and P = 0.023, respectively), global RNFLT (P = 0.004 and 0.012, respectively), RNFLT of the temporal quadrant (P < 0.001 and P = 0.042, respectively) and PE grade (P < 0.001 and P = 0.035, respectively). CONCLUSION: The NLR and PLR values and their associations with BCVA, RNFLT, and PE support the hypothesis that inflammation is a very important component of the pathogenesis of IIH.